Aplikasi Pembelajaran Berbasis Mobile - Paska Marto Hasugian (Jayapangus Press, 2018)
Current technological developments cannot be avoided from various aspects of both the industrial, governance and education world. One of the most rapid developments in terms of technology is mobile devices or often referred to as mobile with various versions up to smartphones with Android information systems. According to the Indonesian research institute, it is the sixth country for smartphone users in the world to spread users ranging from teenagers to old age. This development certainly has a great impact on the development of users in general students. From the process developed an application with the help of mobile devices with the concept that users in this case students or students can learn without being limited by time and distance. So that the learning process continues well.